2016
DOI: 10.14238/sp15.6.2014.345-52
|View full text |Cite
|
Sign up to set email alerts
|

Manfaat Pemberian ASI Eksklusif dalam Pencegahan Kejadian Dermatitis Atopi pada Anak

Abstract: D ermatitis atopi (DA) adalah kelainan inflamasi kronis pada kulit yang sering terjadi pada anak. Masalah ini menjadi semakin penting karena prevalens yang meningkat di seluruh dunia.1-5 Prevalens DA pada anak meningkat 2-3 kali selama tiga dekade terakhir terutama di negara maju, seperti di Amerika Serikat, Jepang, dan negara-negara di Eropa Barat (10%-20%).3-9 Prevalens DA yang lebih rendah terdapat pada negara berkembang di Eropa Timur, Afrika, dan Asia Tengah.3,5,10 Sebuah studi kohort di Jakarta pada tahu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 36 publications
2
7
0
4
Order By: Relevance
“…13 Miyake et al and Pohlabein et al found in their study that breastfeeding may induce acute dermatitis among children without family history of atopic dermatitis. 9,14 Similar results were also found by Halim et al Their study found no significant effect of exclusive breastfeeding as a preventive measure against atopic dermatitis in children. 14 Atopic dermatitis has a broad clinical spectrum and varies among different age groups.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…13 Miyake et al and Pohlabein et al found in their study that breastfeeding may induce acute dermatitis among children without family history of atopic dermatitis. 9,14 Similar results were also found by Halim et al Their study found no significant effect of exclusive breastfeeding as a preventive measure against atopic dermatitis in children. 14 Atopic dermatitis has a broad clinical spectrum and varies among different age groups.…”
Section: Introductionsupporting
confidence: 72%
“…9,14 Similar results were also found by Halim et al Their study found no significant effect of exclusive breastfeeding as a preventive measure against atopic dermatitis in children. 14 Atopic dermatitis has a broad clinical spectrum and varies among different age groups. Acute signs include pruritic excoriated erythematous papules with serous exudate while chronic signs include lichenification, papules and excoriation.…”
Section: Introductionsupporting
confidence: 72%
“…Sekitar 80% anak yang menderita dermatitis atopik tersebut akan mengalami asma dan rhinitis alergi di kemudian hari. [3][4][5][6] Sementara itu, data dermatitis atopik pada tahun 1996-2000 di RSUP dr. Kariadi menunjukkan insidens tertinggi dialami oleh anak berusia kurang dari 5 tahun (62.6%), dan diikuti oleh kelompok usia 5-14 tahun (37,4%). 7 Dermatitis atopik merupakan penyakit multifaktor yang berkaitan dengan genetik, respons imun terhadap antigen, gaya hidup (pola makan), dan lingkungan.…”
Section: Pendahuluanunclassified
“…Dalam penatalaksanaan dermatitis atopik, sangat penting untuk melakukan modifikasi faktor risiko agar dermatitis atopik berkurang kekerapan rekurensinya. 5,8 Rasa gatal berulang yang dialami oleh anak dengan dermatitis atopik akan menimbulkan berbagai gangguan, mulai dari sulit tidur, rewel, gangguan pola makan, gangguan pertumbuhan, dan gangguan konsentrasi. 6 Banyak faktor yang berperan dalam insidens dermatitis atopik serta akibat yang ditimbulkannya, sehingga pencegahan dermatitis atopik sangat penting dilakukan.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation